Mixed emotions in multiview face emotion recognition - Goodarzi, Farhad; Rokhani, Fakhrul Zaman; Saripan, M. Iqbal; Marhaban, Mohammad Hamiruce (IEEE, 2017)
The problem of recognizing and discriminating mixed emotions in multi view faces using a web camera is discussed in this paper. Based on the literature, there are mainly seven basic emotions that humans can express and understand. However, in some faces in databases, there are characteristics of two or more of this basic emotions. The two databases of BU3DFE and UPM3DFE were tested for mixed emotion accuracy using the proposed multi view face emotion recognition method. The results show an improvement over existing works in mixed emotions recognition.